Influence of Plantation Establishment on Discharge Characteristics in a Small Catchment of Tropical Forest - Siti Aisah Shamsuddin; Zulkifli Yusop; Shoji Noguchi (International Journal of Forestry Research)
A study was conducted on the impact of forest clearance on discharge from newly established Hopea odorata plantations catchment (14.4 ha). The stands were two years old when this study commenced in year 2006 and the data collection was carried out for two years. The forested catchment (C3) was clear-cut during the preparation of the forest plantation and catchment C1 was left undisturbed. Discharge and rainfall were measured continuously for two years. The discharge measured from years 1997 to 2003 was used also to determine the water yield before and after forest clear-cut. This study showed that the plantation catchment is more responsive to storm with higher total water yield than in the forested catchment. The effect of forest clear cutting to discharge was clearly shown by the increment in the amount following the clear-cut activities and time taken for the recovery of the discharge back to its original state was almost three years. The peak discharge in C3 also was affected in which the biggest change was obtained during the forest clear-cutting period compared with during calibration and after clearing periods. This study is useful as basis for improving the existing guidelines on forest plantation establishment.